The concept of eco-friendly schools: The application of science education in shaping children's characters to the environment. Issue 1 (February 2021) - Muafiah, Evi; Afifah, Anis; Nurohman, Dede; Huda, Syamsul; Siswadi,
Abstract: This research was conducted to complement the existing learning by mapping carefully the child-friendly learning model applied at the Pelangi Alam School, Ponorogo, and how schools instill good habits through environmentally friendly exploration activities carried out in each lesson. This study used a qualitative phenomenological method by trying to understand the concept of environmental love by providing science and applying it to the environment. In addition, students also practiced science in understanding how the process of environmental care is through the implementation of the Environmental Green School program Pelangi Alam School, Ponorogo. The data sources of this research were the principal and 2 teachers. Data collection techniques were carried out by observing the reality of school activities, interviews about understanding the concept of Green School Environment as an effort to anticipate radicalism in schools and documentation. Based on the results of the research, the concept of Eco-Friendly Schools can help in developing positive characters. In general, students will follow the behavior that has been taught by the teacher. This continuous behavior will give a new habit which eventually become attached to the formation of the natural character of the students.